Evaluation of bore exit quality for fibre reinforced plastics including delamination and uncut fibres. (January 2016) - Voß, Robert; Henerichs, Marcel; Rupp, Stephan; Kuster, Friedrich; Wegener, Konrad
Abstract: Analyses of the bore exit in Carbon Fibre Reinforced Plastics (CFRP) represent a common method to evaluate workpiece quality non-destructively. The delamination factor F d, developed by Chen (International Journal of Machine Tools and Manufacture, 37 (1997) 1097) has been established, being a straightforward measureable variable representing the bore quality. Within this paper the advantages and disadvantages of the delamination factor F d, the adjusted delamination factor F da by Davim et al. (Composites Science and Technology, 67 (2007) 1939) and the equivalent delamination factor F ed by Tsao et al. (The International Journal of Advanced Manufacturing Technology, 59 (2012) 617) as well as the delaminated area A d at the bore exit are discussed. In unidirectional CFRP material, which tends to show single delaminated fibres, spalling and uncut fibres the commonly used delamination factors F d, F da and F ed are unsuitable to describe the bore quality. Five separate damage values combined to a Quality function Q d are proposed, allowing a reliable evaluation of the machined bore quality especially for unidirectional CFRP. The suitability of Q d is demonstrated on a drilling series in CFRP and analysed by a robust, operator independent Matlab © tool. In most of the former research, the thrust force increase is used to describe the tool wear. The theoretical critical thrust force of the material determined by Ho-Cheng and Dharan (Journal of Manufacturing Science and Engineering, 112 (1990) 236) as well as Tsao and Hocheng (International Journal of Machine Tools and Manufacture, 43 (2003) 1087) defines the end of tool life time. The presented approach of Q d offers the possibility to define the expected residual tool life time based on the actual bore exit quality. It contains five bore exit quality factors enabling adaption to different material properties. To proof the applicability, Q d is compared to the common delamination factors, the progress of tool wear and the thrust force increase which is known to correlate with the bore exit quality in CFRP machining.